Community-based initiatives and Spanish as a Heritage Language in Germany - Elizondo Romo, Mariel (HCIAS working papers on Ibero-America, 2025)
Migration from Spanish-speaking countries into Germany has increased during the last 30 years. Demographic studies indicate that a large proportion are young women migrating to marry German nationals and start families (Loureda Lamas et al. 2020). The study looks at what motivates these migrants to create initiatives to maintain Spanish as a heritage language. Using a narrative ethnographic approach (He 2021), I analyze interviews of founders of 6 community initiatives of Spanish as a heritage language in Germany to understand what their motivations are and what roles they play in their communities. I argue that the people who create these associations are engaging in a strategy of “commoning care work” (Dengler & Lang 2021) by taking the task of teaching the family language, understood to be invisible work (Okita 2002), outside the home domain.
Gesehen am 23.06.2025